Differences in Saliva pH of Users and Non-users of Fixed Orthodontic Wire in Dental Students (FKG UNPRI) - Rusip, Gusbakti; Member Reni Purba; Fitri Inriani Silaban (HM Publisher, 2024)
Fixed orthodontics corrects malocclusion, which can compromise facial aesthetics. Nevertheless, the utilization of this orthodontic apparatus presents the potential for plaque buildup stemming from the colonization of microorganisms, which may influence the pH of saliva. The purpose of the research was to compare the pH levels of the saliva of individuals who utilized fixed orthodontic wires to those who did not. The design of this survey-analytic, cross-sectional study is survey-based. Sixty-two FKG UNPRI students who satisfied the inclusion and exclusion criteria comprised the sample. We divided these students into two groups: one group utilized fixed orthodontic wires, while the other group did not. To determine the pH of saliva, submerge the pH paper tip into the saliva. If a color change occurs, modify the pH paper using a saliva pH indicator. Following the collection of all the data, an analysis of the data was conducted utilizing the Mann-Whitney statistical test. The study findings indicated that individuals who utilized fixed orthodontic wires had an average saliva pH of 6.16 ± 0.735, whereas those who did not use the devices had a saliva pH of 7.19 ± 0.543. According to the findings of the Mann-Whitney statistical test, a statistically significant distinction in saliva pH was observed between individuals who utilized fixed orthodontic wires and those who did not (p = 0.000; p<0.05). In conclusion, users of fixed orthodontic wires have, on average, a lower salivary pH than non-users.